Mass Transfer and Heat Generation Effects on MHD Free Convection Flow past an Inclined Vertical Surface in a Porous Medium - Machireddy Gnaneswara Reddy; N.B Reddy (Journal of Applied Fluid Mechanics, 2011)
A steady two-dimensional MHD free convection and mass transfer flow past an inclined semi-infinite vertical surface in the presence of heat generation and a porous medium has been studied numerically. The governing partial differential equations are reduced to a system of ordinary differential equations by introducing similarity transformations. The non-linear similarity equations are solved numerically by applying the Runge-Kutta method of fourth order with shooting technique. The numerical results are presented graphically for different values of the parameters. Finally, the numerical values of the local skin-friction coefficient, local Nusselt number and Sherwood number are shown in Table 1.